'Managing' the rights of gays and lesbians: Reflections from some South African secondary schools. (March 2014) - Bhana, Deevia
Against the backdrop of South Africa's policies that guarantee equality on the basis of sexual orientation, this article documents the ways in which school managers negotiate and contest the rights of gays and lesbians at school, analysing the implications. It draws on a queer approach which recognizes relations of heterosexual domination and subordination as well as the material and social realities through which such relations are produced. Of importance, the study finds that the political emphasis on rights has positive effects for raising the homosexual agenda at schools. Yet, this is not the only means through which rights are managed. Discrimination, sexual denial and religious intolerance combined with racialized and cultural practices point to severe restrictions. Nonetheless, the article provides important insights for educational management noting the broadening options amid political and policy emphasis on schools' responsibilities for sexual rights.